Study of four plants with traditional medicinal use from Costa Rica’s Huetar Norte and Huetar Atlantica regions - Moreira-González, Ileana (2014)
The present research sought to advance the domestication of Phyllanthus niruri (chanca piedra), Senna reticulata (Saragundi), Pettiveria Alliaceae (Ajillo) and Phyllanthus acuminatus (Chilillo), their phytochemistry and biological potential using techniques towards the establishment of protocols that ensure their proper use. At the same time, good practices were promoted among communities from the Huetar Norte and Huetar Atlantica regions, so to support the use of these plants in a sustainable way. The transfer of results regarding good practices as well as knowledge on polyphenol contents and biological potential to the target groups sought to support capacity building looking to improve their insertion in productive chains within communities, as an alternative livelihood, thus providing, in addition to academic scientific development through basic research results, socioeconomic and environmentally sustainable development.